FEATURES OF THE MODEL OF A SPECIALIZED GEOSPATIAL DATABASE FOR VISUALIZING INDICATORS OF HUMAN SOCIO-ECONOMIC SECURITY IN WARTIME CONDITIONS - Zakharii S. Varnalii; Oleksii P. Fedchenko; Ihor V. Pampukha; Ihor V. Tolok (Academy Review)
The socio-economic security of the state is not only a guarantee of its citizens’ safety but also a guarantee of a decent standard of living. Studying the impact of military conflicts on human social security reveals weaknesses in the implementation of state policy in the political, economic, and social spheres. This is especially relevant in the context of russian aggression against Ukraine. In wartime conditions, it becomes necessary to use new technologies for managing socio- economic processes, particularly for analysis and decision-making. Geographic information systems (GIS) are a key tool in this process. They enable the analysis of situations, the prediction of event developments, and the formulation of optimal action strategies. Modern geographic information systems, particularly ArcGIS, offer a full range of tools for collecting, organizing, and analyzing geographic data that characterize socio-economic aspects of development at local and global levels. They allow for the creation of effective systems for socio- economic monitoring and decision-making support. The article analyzes the features of a geospatial database model for visualizing indicators of socio- economic security for individuals in wartime. It examines the role of GIS in studying the impact of war on individual socio-economic security and proposes a model structure for a specialized geospatial database to visualize socio-economic indicators of occupied regions using the ArcGIS system as an effective decision-making support tool in management. A specialized geospatial database provides the foundation for visualizing indicators of socio-economic security in wartime by combining GIS capabilities as an effective tool for researching the impact of full-scale war on individual socio-economic security. This includes the promptness, completeness, and quality of informational and spatial support for management and decision-making processes. Services, thematic web maps, and web applications based on a specialized geospatial database and published on the ArcGIS Online portal highlight key components impacting socio-economic security in full-scale war conditions. They provide comprehensive visual information essential for decision-making. Most of these elements dynamically update with data changes, support data filtering, and present only the most important and relevant information for decision-makers on the dashboard.